PREVENTION OF HEALTHCARE ASSOCIATED INFECTIONS BY COMPLIANCE TO BLOOD BORNE PATHOGENS TRANSMISSION PROTOCOLS IN THE DENTAL OFFICES IN IASI - Magda Calina Barlean; Eugenia Popescu; Carina Balcos; Livia Bobu; Georgiana Macovei; Lucia Barlean (Romanian Journal of Oral Rehabilitation, 2019)
The aim of the study was to evaluate the level of training and compliance with administrative and clinical infection prevention recommendations in the dental settings in Iasi. Material and methods. A questionnaire based study was initiated including 93 dentists in Iasi. Results. 91,5% of the dentists wish to be trained in infection control, and 78,7% consider important the presence of a coordinator in this domain. In no dental office the compliance to Standard Precautions is evaluated by planned activities. 78,4% of the subjects are immunized against Hepatitis B . The sterilization equipment’s maintenance is performed and documented in 87,2% of the settings. In 80,5% of them the necessary supplies for hand hygiene are easily accessible. 74,7% of the dentists wear the full protective equipment. Written policies and procedures for the cleaning and disinfection of reusable instruments and environmental surfaces are available in 78,2% , respectively 21,3% of the dental offices. In all dental settings a chemical indicator is used for the sterilisation monitoring. Conclusions. The investigation findings highlighted the need for continuous dental staff training by an infection control coordinator based on assessing compliance with recommended policies and practices.